2000
DOI: 10.1142/s0192415x00000416
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pharmacological Studies on Liver Disease Treated with Kampo Herbal Medicine

Abstract: Hepatitis C virus (HCV) infection frequently causes chronic hepatitis, which is linked to the development of liver cirrhosis and hepatocellular carcinoma. Most physicians who practice Kampo medicine in Japan have observed that Kampo medicine can be as effective as interferon therapy in the treatment of chronic hepatitis C. In the present study, to evaluate the effect of Kampo medicine on chronic hepatitis C, clinical treatment was assessed in short-term and long-term study, and it was shown that ninjin-yoei-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…Fibrotic liver disease In Japan, recommended for hepatitis B virus TJ-41 50,51 Herbal mixture, induces cellular apoptosis via P 53. Hepatocellular carcinoma TJ-108 51 Herbal mixture with active compound gomisin A. Antiviral Hepatitis C virus Liv-52 52 Herbal mixture-hepatoprotective In India, alcohol-induced liver disease Phyllanthus amarus 54,55 Extract inhibits hepatitis B viral polymerase by inhibiting the virus enhancer I activity-complexes transcription factors…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…Fibrotic liver disease In Japan, recommended for hepatitis B virus TJ-41 50,51 Herbal mixture, induces cellular apoptosis via P 53. Hepatocellular carcinoma TJ-108 51 Herbal mixture with active compound gomisin A. Antiviral Hepatitis C virus Liv-52 52 Herbal mixture-hepatoprotective In India, alcohol-induced liver disease Phyllanthus amarus 54,55 Extract inhibits hepatitis B viral polymerase by inhibiting the virus enhancer I activity-complexes transcription factors…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…A traditional Chinese prescription, Ninjinyoeito (TJ-108), has been reported to reduce serum transaminase levels, increased levels of which are a symptom of chronic hepatitis C, and leads to viral seroconversion. Among the herbal components of Ninjinyoeito, Schisandra fruit and its lignan component, gomisin A, have shown protective effects against immunological hepatopathy [22]. We have previously reported that nine herbal extracts exhibit therapeutic anti-HSV-1 activity in a murine infection model [13].…”
Section: Discussionmentioning
confidence: 99%
“…Schisandra chinensis Turz Baill of the Magnoliaceae ( Wuweizi in Chinese) (SC) is widely used as a valuable phytomedicine in China, Korea, and Japan to treat dysfunctional livers, lungs, hearts, and kidneys [9] and for chemical/viral hepatitis [10], [11]. Dibenzocyclooctadiene lignans isolated from SC (abbreviated as SCLs) include schizandrin, deoxyschisandrin (schisandrin A, SA), gomisins, schisandrol B, γ-schisandrin, wuweizisu B and C, and schisantherin C [12].…”
Section: Introductionmentioning
confidence: 99%